Salt for the earthen oven revisited - Pilch, John J. (HTS teologiese studies, 2011)
The symbolic interpretation of the salt sayings in the New Testament (Mt 5:13; Mk 9:42–50; Lk 12:49–53; 14:34–35) is best based on the long-standing cultural practice of using salt as a catalytic agent to burn dung, the common fuel for the typical earthen oven used by peasants even to this day. Seasoning and preservation are culturally inappropriate.